2022
DOI: 10.1111/fcp.12838
|View full text |Cite
|
Sign up to set email alerts
|

Photobiological effect of eugenol‐derived 3‐benzoylcoumarin associated with led lights against MDR microorganisms

Abstract: The problem of antibiotic resistance by bacteria threatens human health. Therefore, studies in this area seek alternatives to circumvent it. The study with coumarins and eugenol has already proven that these classes of compounds act against bacteria. In this same aspect, exposure to LED also shows a bactericidal effect. Seeking a possible enhancement of this effect, the present work studied coumarins derived from eugenol in association with LED to investigate the bactericidal effect. Four compounds were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Coumarins with the same C-3 substitutions as the compounds evaluated in the present study showed synergism with antibiotics. Against S. aureus, coumarins with benzoyl and 4-nitrobenzoyl radicals caused the most significant potentiation of norfloxacin, corroborating our results [32].…”
Section: Discussionsupporting
confidence: 90%
“…Coumarins with the same C-3 substitutions as the compounds evaluated in the present study showed synergism with antibiotics. Against S. aureus, coumarins with benzoyl and 4-nitrobenzoyl radicals caused the most significant potentiation of norfloxacin, corroborating our results [32].…”
Section: Discussionsupporting
confidence: 90%